Seismic failure probability of a 400 kV power transformer using analytical fragility curves. (December 2016) - Zareei, Seyed Alireza; Hosseini, Mahmood; Ghafory-Ashtiany, Mohsen
Abstract: Recent earthquakes have shown that Electrical Power Substations' equipment are seismically vulnerable, resulting in disruption of power supply in many cases, and therefore their seismic vulnerability evaluation is of great importance. Power transformers (PTR) are critical elements in a power substation, so their proper functioning during and after earthquakes is essential. In this study first, seismic vulnerability of PTRs in past earthquakes is reviewed and failure modes are discussed, then 3D finite element modeling and time-history analysis were performed using 99 three-component original accelerograms of ground motions. Seismic analytical fragility curves of a 400 kV PTR are obtained in two damage states using Multiple Stripes Analysis method which estimates the fragility values while minimizing the required number of structural analysis. The results show that using extra high strength C130 porcelain, the PTR's bushing wouldn't encounter with moderate damage and it might be also acceptable for ground motions with peak ground acceleration (PGA), lower than 0.4 g. It can also be expressed that utilizing specific seismic considerations such as base-isolation, providing dampers or using composite bushing is necessary for PTR's porcelain bushing in seismic regions (PGAs ≥ 0.5 g). Highlights: Seismic vulnerability of PTRs in past earthquakes is evaluated. 3D finite element modeling and time-history analyses were performed for of a 400 kV Power Transformer. Seismic analytical fragility curves are obtained using Multiple Stripes Analysis. Utilizing specific seismic considerations is necessary for power transformers in seismic regions (PGAs ≥ 0.5 g).